Accessory Mineral Eu Anomalies in Suprasolidus Rocks: Beyond Feldspar - Holder, R. M.; Yakymchuk, C.; Viete, D. R. (Geochemistry, Geophysics, Geosystems, 2020)
Accessory mineral Eu anomalies (Eu/Eu*) are routinely measured to infer changes in the amount of feldspar over time, allowing accessory mineral U‐Pb dates to be linked to the progressive crystallization of igneous and metamorphic rocks and, by extension, geodynamic processes. However, changes in Eu/Eu* can reflect any process that changes the relative availability of Eu2+ and Eu3+. We constructed partitioning budgets for Sm, Eu2+, Eu3+, and Gd in suprasolidus metasedimentary rocks to investigate processes that can influence accessory mineral Eu anomalies. We modeled three scenarios: (1) closed‐system, equilibrium crystallization; (2) fractionation of Eu by feldspar growth during melt crystallization; and (3) removal of Eu by melt extraction. In the closed‐system equilibrium model, accessory mineral Eu/Eu* changes as a function of fO2 and monazite stability; Eu/Eu* changes up to 0.3 over a pressure‐temperature range of 4–12 kbar and 700–950°C. Fractionation of Eu by feldspar growth is modeled to decrease accessory mineral Eu/Eu* by ~0.05–0.15 per 10 wt% feldspar crystallized. Melt extraction has a smaller effect; removal of 10% melt decreases accessory mineral Eu/Eu* in the residue by ≤0.05. Although these models demonstrate that fractionation of Eu by feldspar growth can be a dominant control on a rocks u budget, they also show that the common interpretation that Eu/Eu* only records feldspar growth and breakdown is an oversimplification that could lead to incorrect interpretation about the duration and rates of tectonic processes. Consideration of other processes that influence Eu anomalies will allow for a broader range of geological processes to be investigated by petrochronology.Plain Language SummaryMetamorphic rocks—rocks in which new minerals grew in response to increase in pressure and temperature related to deep burial or subduction—and igneous rocks—rocks that formed as magmas cool and crystallize—provide a direct record of how Earth’s continents have moved and changed through time. To read this record, ...